2019
DOI: 10.1186/s12981-019-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy and the associated factors among people living with HIV/AIDS in Northern Peru: a cross-sectional study

Abstract: Background There are approximately 72,000 people living with HIV/AIDS (PLHIV) in Peru. Non-adherence to antiretroviral therapy (ART) is the most important factor for therapeutic failure and the development of resistance. Peru has achieved moderate progress in meeting the 90-90-90 targets, but only 60% of PLHIV receiving ART are virally suppressed. The purpose of this study was to understand ART adherence in the Peruvian context, including developing sociodemographic and clinical profiles, evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
1
14
2
5
Order By: Relevance
“… 31 , 45 Moreover, the level of adherence to ART is also higher than the studies conducted in Peru (41.7%), and Brazil (71.6%). 46 , 47 On the other hand, this finding is lower than the studies conducted in Debre Birhan (95.5%) and Nepal (87.4%). 32 , 48 …”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“… 31 , 45 Moreover, the level of adherence to ART is also higher than the studies conducted in Peru (41.7%), and Brazil (71.6%). 46 , 47 On the other hand, this finding is lower than the studies conducted in Debre Birhan (95.5%) and Nepal (87.4%). 32 , 48 …”
Section: Discussioncontrasting
confidence: 63%
“…This study showed that children having TB/HIV co-infection increase the level of poor adherence by 3.80 times than children without TB co-infection (AOR=3.80, 95% CI (1.41, 10.1)) which is in line with other studies. 43 , 47 This might be due to the summative effect of suffering from two chronic conditions, associated with stigma and discrimination that require clinical management for an entire life. In addition to this, medication for confection, treatment, and ART together can contribute to increased pill burden, drug–drug interactions, and more adverse drug effects, all of which are capable of hindering adherence to antiretroviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is, however, better than in studies done in Nigeria (74.2%), 26 Yirgalem Hospital of Ethiopia (63.8%), 27 and Peru (41.7%). 28 The explanation for this variation, particularly from the study in Peru, may be differences in sample sizes, with a small sample being used in Peru, and differences in the tools used for assessing adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A digitalised appointment system could assist in providing this service on a larger scale in Loreto [54]. Instruments to measure adherence should be developed [55].…”
Section: Discussionmentioning
confidence: 99%